Respiratory Mononuclear Phagocytes in Human Influenza A Virus Infection: Their Role in Immune Protection and As Targets of the Virus - Vangeti, Sindhu; Yu, Meng; Smed-Sörensen, Anna (Frontiers in Immunology, 2018)
Emerging viruses have become increasingly important with recurrent epidemics. Influenza A virus (IAV), a respiratory virus displaying continuous re-emergence, contributes significantly to global morbidity and mortality, especially in young children, immunocompromised and elderly people. IAV infection is typically confined to the airways and the virus replicates in respiratory epithelial cells but can also infect resident immune cells. Clearance of infection requires virus-specific adaptive immune responses that depend on early and efficient innate immune responses against IAV. Mononuclear phagocytes (MNPs), comprising monocytes, dendritic cells and macrophages, have common but also unique features. In addition to being professional antigen presenting cells, MNPs mediate leukocyte recruitment, sense and phagocytose pathogens, regulate inflammation and shape immune responses. The immune protection mediated by MNPs can be compromised during IAV infection when the cells are also targeted by the virus, leading to impaired cytokine responses and altered interactions with other immune cells. Furthermore, it is becoming increasingly clear that immune cells differ depending on their anatomical location and that it is important to study them where they are expected to exert their function. Defining tissue-resident MNP distribution, phenotype and function during acute and convalescent human IAV infection can offer valuable insights into understanding how MNPs maintain the fine balance required to protect against infections that the cells are themselves susceptible to. In this review, we delineate the role of MNPs in the human respiratory tract during IAV infection both in mediating immune protection and as targets of the virus.